(untitled) (Archives of Mechanics - Test, 2014)
In this work, we apply the fractional order theory of thermoelasticity to a 1D problem of an infinitely long cylindrical cavity. Laplace transform techniques are used to solve the problem. Numerical results are computed and represented graphically for the temperature, displacement and stress distributions.